Kompetensi Paralegal dalam Bantuan Hukum: Dampak Putusan MA Nomor 22 P/HUM/2018 dan Prospek Regulatif - Tobi Haryadi; Rianda Riviyusnita (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Paralegals play a vital role in expanding access to justice for the poor and vulnerable groups, particularly in remote areas underserved by lawyers. However, their role was restricted following the Supreme Court Decision Number 22 P/HUM/2018, which annulled provisions in the Ministry of Law and Human Rights Regulation Number 1 of 2018 regarding paralegals’ authority to assist clients during investigations and court proceedings. This study aims to analyze the legal impact of the decision on paralegals’ competencies and explore future regulatory prospects to ensure the effectiveness of legal aid services. Using a normative juridical method through statutory and case law approaches, the study finds that a legal vacuum has emerged, hindering paralegals' contribution to structural legal aid. Therefore, regulatory reform is necessary to provide legal recognition to paralegals' roles with clear authority limitations and an accountable certification mechanism.